Sleeping in moderate hypoxia at home for prevention of acute mountain sickness (AMS): a placebo-controlled, randomized double-blind study - Dehnert, Christoph; Böhm, Astrid; Grigoriev, Igor; Menold, Elmar; Bärtsch, Peter (Wilderness & environmental medicine, 2014)
Objective - Acclimatization at natural altitude effectively prevents acute mountain sickness (AMS). It is, however, unknown whether prevention of AMS is also possible by only sleeping in normobaric hypoxia. - Methods - In a placebo-controlled, double-blind study 76 healthy unacclimatized male subjects, aged 18 to 50 years, slept for 14 consecutive nights at either a fractional inspired oxygen (Fio2) of 0.14 to 0.15 (average target altitude 3043 m; treatment group) or 0.209 (control group). Four days later, AMS scores and incidence of AMS were assessed during a 20-hour exposure in normobaric hypoxia at Fio2 = 0.12 (equivalent to 4500 m). - Results - Because of technical problems with the nitrogen generators, target altitude was not achieved in the tents and only 21 of 37 subjects slept at an average altitude considered sufficient for acclimatization (>2200 m; average, 2600 m). Therefore, in a subgroup analysis these subjects were compared with the 21 subjects of the control group with the lowest sleeping altitude. This analysis showed a significantly lower AMS-C score (0.38; 95% CI, 0.21 to 0.54) vs 1.10; 95% CI, 0.57 to 1.62; P = .04) and lower Lake Louise Score (3.1; 95% CI, 2.2 to 4.1 vs 5.1; 95% CI, 3.6 to 6.6; P = .07) for the treatment subgroup. The incidence of AMS defined as an AMS-C score greater than 0.70 was also significantly lower (14% vs 52%; P < .01). - Conclusions - Sleeping 14 consecutive nights in normobaric hypoxia (equivalent to 2600 m) reduced symptoms and incidence of AMS 4 days later on exposure to 4500 m.
Gesehen am 16.09.2020